Machine learning, image processing, network security and data sciences : second International Conference, MIND 2020, Silchar, India, July 30-31, 2020, Proceedings.: second International Conference, MIND 2020, Silchar, India, July 30-31, 2020, Proceedings. Part II (2020) - Unknown
No abstract available